Introducing retakaful pool for takaful operators - Wan Zamri Wan Ismail (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
The aim of this research is to explore the concept and practice of retakaful pool as a viable and practicable alternative to reduce the high dependence on retakaful operators from the current retakaful practices. The conventional approach adopted by takaful operators is to heavily leverage on the services of retakaful to manage the risk exposures of the business. The current blanket approach to retakaful is not cost efficient and does not offer optimal benefits to the takaful operators as trustees of the takaful fund. Being established on a different conceptual foundation, takaful as a Shariah compliant risk management tool should, in its operational framework, be able to provide better alternative solutions in managing the takaful risks exposures in other ways besides the normal retakaful practices. This research will undertake both the qualitative and quantitative approach. For this purpose, the various theoretical foundations on insurance, reinsurance, takaful and retakaful are reviewed as well as analysis of published data of Bank Negara Malaysia on takaful and insurance and structured interview questionnaire of takaful operators are undertaken. The shortfall in the current retakaful practices can be addressed by the establishment of the proposed retakaful pool where optimal benefits may be obtained by the takaful operators in their management of retakaful towards strengthening the takaful risk fund in particular and for the advancement of the takaful industry in general.